1989
DOI: 10.1038/bjc.1989.371
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of vincristine binding to plasma membrane vesicles from daunorubicin-resistant Ehrlich ascites cells by multidrug resistance modulators

Abstract: Summary The multidrug resistance (MDR) phenotype is presumed to be mostly dependent on changes in the resistant cell plasma membrane, notably the emergence of a 170 kDa glycoprotein called P-glycoprotein, which facilitate increased drug efflux. We have previously demonstrated that ATP-enhanced binding of vincristine (VCR) to plasma membrane vesicles is much greater in MDR than in wild type cells. The present study has shown that VCR binding to MDR Ehrlich ascites tumour cell plasma membrane vesicles is inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Furthermore, although verapamil at a 5-fold molar excess increases daunorubicin accumulation in EHR2/DNR + at least 400% (Friche et al, 1987), daunorubicin does not increase verapamil accumulation even at 10-fold molar excess (Figure 3), a result which is in agreement with Kessel (1986). Vincristine however, whose accumulation in EHR2/DNR + cells is increased at least 500% by a 10-fold molar excess of verapamil (Sehested et al, 1989b) is only able to increase verapamil accumulation by 37% at a similar molar excess (Figure 3). Thus, daunorubicin appears to interact differently with Pglycoprotein in EHR2/DNR + cells compared to azidopine, verapamil and vincristine.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Furthermore, although verapamil at a 5-fold molar excess increases daunorubicin accumulation in EHR2/DNR + at least 400% (Friche et al, 1987), daunorubicin does not increase verapamil accumulation even at 10-fold molar excess (Figure 3), a result which is in agreement with Kessel (1986). Vincristine however, whose accumulation in EHR2/DNR + cells is increased at least 500% by a 10-fold molar excess of verapamil (Sehested et al, 1989b) is only able to increase verapamil accumulation by 37% at a similar molar excess (Figure 3). Thus, daunorubicin appears to interact differently with Pglycoprotein in EHR2/DNR + cells compared to azidopine, verapamil and vincristine.…”
Section: Discussionsupporting
confidence: 77%
“…EHR2/DNR + cells have all the characteristics associated with the multidrug resistance phenotype including cross resistance to vinca alkaloids and decreased drug accumulation (Skovsgaard, 1978), modulation by verapamil (Friche et al, 1987), and increased expression of P-glycoprotein (Sehested et al, 1989a (Skovsgaard, 1977). Experiments with azidopine were performed in the dark.…”
Section: Cell Linesmentioning
confidence: 99%
“…Further studies found that the P-gp inhibiting activity is shared by many other calcium channel blockers such as, diltiazem [38] , bepridil [40] , nicardipine, nifedipine [38] , felodipine, and isradipine [41] . In addition, non-calcium channel blockers such as calmodulin antagonists (trifluorperazine, clopenthixol, trifluopromazine, and flupenthixol) [38] , chlorpromazine and prochlorperazine, indole alkaloids, the anti-malarial quinine and the anti-arrhythmic quinidine [42] demonstrated P-gp inhibiting activity. P-gp inhibiting agents are pharmacologically active in vitro in concentration range from (1 to 50 μM).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of structural cationicity is a pivotal structure distinction between CM channel endocytosing small molecule xenobiotic hydro-lipophiles such as vincristine and doxorubicin that induce non-association of microtubule γ-tubulin at MM VDAC and result in CM mitochondrial anchorage non-mobility-mediated MM disruption/mitochondrial-mediated apoptosis, in contrast to those that do not but with instead have mitogenic potential, which is the case for ouabain (102), a non-cationic circumferentially carbonylated/hydroxylated hydro-lipophile endocytoser of the Na + /K + ATPase, with potential to cause epithelilal-to-mesenchymal transformation (EMT) as well as tumoropropagation via CM receptor endocytosis-mediated (Pseudo) 3ary indirect pressuromodulation (17). The xenobiotics of this category induce endocytosis of their respective channels, the Ca 2+ channel (123 kDa N/P/Q α subunit MW) (92) (vincristine > verapamil) and the Na + /K + ATPase channel (112 kDa α subunit MW) (103) (ouabain, momensin, doxorubicin and daunorubicin), which are present on the CM in juxtaposition to one another and to P-gp (non-glycosylated MW 140 kDa) (104), whereby, ligand-mediated Ca 2+ channel-endocytosis of associated CM results in concomitant endocytosis of P-gp (105), that decreases immediate P-gp CM expression. Thus, P-gp overexpression and associated multi-drug resistance emerges, secondarily, in surviving tumor cells with lower compliance set points than before therapy due to the increased transcription of higher MW proteins such as P-gp (11), in which case, intra-cellularly accumulating drug fraction is extruded by its ability to interact with intra-CM P-gp α-helixes viz a viz hydro-lipophile incorporating lipophilicity, and induce, α-helix apposition pump functionality (104).…”
Section: Resultsmentioning
confidence: 99%